Innovated design,‎‏‎ simulation and ‎evaluation of potato ‎harvester ‎excavation and separation conveyors - Issa, Ibrahim Issa Mohamed; Zhang, Zhaoguo; El-Kolally, Wael; Wang, Fa’an; Wang, Yuan (International Journal of Agricultural and Biological Engineering, 2025)
To address problems encountered in current potato harvesting machines in hilly and ‎mountainous ‎areas, such as potato damage, poor adaptability, low operational efficiency, and ‎the inability of ‎‎traditional harvesters to meet the requirements in these ‎areas, a new potato ‎harvester equipped with excavation and ‎a multi-stage separation conveyor‎ was developed by using design and ‎simulation programs as an innovative way to identify the best operating factors. SolidWorks ‎Software was used to design an excavation and ‎a multi-stage separation conveyor. ANSYS ‎Workbench ‎‎machine ‎static structure analyzed stress, strain, and deformation. The working process of soil ‎and tuber ‎separation ‎was tested and kinematically analyzed by EDEM-RecurDyn and a 5F01M camera. A field ‎‎experiment was ‎also conducted on the machine under several factors: working speed (W)‎, ‎‎excavation depth (D), ‎vibration intensity level (V), and conveyor inclination angle (N)‎‏.‏‎ ‎The ‎quadratic regression orthogonal rotating combination experiment tested four factors with five ‎levels.‎‏ ‏The results of the ‎non-load ‎experiment showed that the lowest ratio of impurities ‎was at the linear speed level (Q3, ‎S5, ‎O3) for the first and second separation conveyor and the ‎side conveyor, respectively. The results ‎‎of the field experiment showed that the optimal parameters were the working speed of 1.05 m/s, ‎‎the digging depth of 180 mm, and the vibration force Ⅱ ‎inclination angle on the screen surface of ‎‎22 ‎degrees, which gave the highest potato lifting rate of 98.8%, and the bruising ‎rate was 1.37%. The ‎damage rate was 1.43%, superior to national industry ‎standards.‎ With its exceptional ‎performance, the machine can effectively meet and solve the challenges of harvesting requirements, making it a ‎valuable tool for the industry.‎ Key words: potato harvester; multi-stage separation conveyors; agricultural machinery; excavating mechanism DOI: 10.25165/j.ijabe.20251802.9164 Citation: Issa I I M, Zhang Z G, ElKolaly W, Wang F A, Wang Y. Innovated design, simulation and evaluation of potato harvester excavation and separation conveyors. Int J Agric & Biol Eng, 2025; 18(2): 132–145.